Analiza politicilor publice din România pentru bolile netransmisibile - Elena Bozdog; Denisa Trif; Nancy J. Thompson; Cătălin Baba (Revista Transilvană de Ştiinţe Administrative, 2018)
Noncommunicable diseases (NCDs) are accountable for more than 63% of the total number of deaths worldwide. National-level policies represent important approaches in reducing the burden of NCDs. The aim of this paper is to evaluate the extent to which Romanian policies addressing the prevention and control of NCDs align with the objectives of World Health Organization (WHO) 2013 – 2020 Global Action Plan for the prevention and control of NCDs. National policies on the prevention and control of NCDs were identified through searches of Google, Google Scholar and official websites. The alignment was determined through content analysis of the documents identified in the first phase. Twenty-two NCD prevention-related policies were identified. The study reports complete alignment for objectives one and three; partial alignment for objective two (8/10 mechanisms), six (4/6 mechanisms) and five (1/6 mechanisms); no alignment for objective four (0/5 mechanisms). National program and strategies are the policies that align with the highest number of mechanisms, and are some of the most recent policies, indicating that the Romanian authorities have been taking initiative in addressing prevention of NCDs by focusing on a broader approach rather than separate initiatives.